A study on the impact of rice price hike on consumers living around Inanam town area / Dionysia James - James, Dionysia (2008)
This research is a study to measure how bad is the impact of the Rice Price Hike to the consumers living around Inanam town area. This study also seeks to gather information and feedback about how the consumers cope with the hike and what are their comments about the current situation and how they wish the authority concerned to act in order to reduce the burden of the consumers. As the most important cereal crop and the staple food of over half of the world's population, rice provides 20% of the world's dietary energy supply. And as the primary dietary source of carbohydrate, rice plays an important role in supplying energy and nutrients to all of us. Based on the overall summary of this research, majority of the respondents strongly agree that the Rice Price Hike really affect their monthly budget and thus have big impact on their daily lives. The negative impacts are such as reducing budget for their savings, family leisure; have to lower quality types of rice due to the hike and etc. However, there are some of the respondents agree that the Rice Price Hike had teach them to be smarter consumers and take positive action like bring their own food to work and change their spending pattern and to be more discipline in their purchase.